Diagnóstico do gerenciamento dos resíduos de serviços de saúde dos grandes geradores no município de São Carlos - SP - Pellegrini, Beatriz Tkaczuk (Universidade Federal de São Carlos, 2024)
Most municipalities in Brazil face problems with solid waste management, considering the stages of segregation at source, collection, packaging, destination and final disposal. Among the different types of waste, health service waste (HSW) stands out as a challenge for many cities. This research focuses on the city of São Carlos/SP and aims to carry out a diagnosis of the management of waste from health services in establishments considered large generators to understand the difficulties and problems faced in relation to segregation at source and packaging, as well as the related costs. The understanding of these factors is relevant because the municipality assumes the full costs of collection, treatment and final disposal of the HSW generated in its territory, burdening the citizens with services that should be paid for by the generators. To meet the objectives, the methodology used comprised (i) the monitoring of the collection of this waste in the large generators, (ii) the analysis of documentary data provided by the City Hall and by the company that performs this management using the standards and laws as a basis for verifying whether the management is meeting the expectations provided for in the legislation and (iii) sending questionnaires to those responsible for the internal management of the HSW to obtain data on how this management is being conducted. The results of the research showed some flaws in the process of segregation and packaging of HSW, as well as the lack of adequate containers for disposal in some establishments; in 100% of the studied generators inadequate segregation and disposal were identified and 25% of these establishments did not have enough adequate containers for the disposal of waste. If, on the one hand, the municipality assumes the costs of disposing of the HSW, on the other hand, the large generators do not demonstrate actions to minimize the volumes generated, contrary to the prioritization established in the National Solid Waste Policy, making it impossible to better manage this waste and consequently burdening the public coffers.
Diagnosis of the management of health service waste from large generators in the city of São Carlos - SP
Keywords: Resíduos sólidos; Serviços de saúde; Resíduos de serviços de saúde; Gerenciamento; Política Nacional de Resíduos Sólidos; Solid waste; Health services; Waste from health services; Management; National Solid Waste Policy; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL